Signalling the loopholes and spreading the trampoline: a relevance-theoretic perspective on ELF communication - Salakhyan, Elena (Journal of English as a lingua franca, 2024)
The paper examines English as a Lingua Franca (ELF) communication from a relevance-theoretic perspective. Communication in English as a Lingua Franca is a type of interaction in which multilingual speakers use a variety of linguistic and non-linguistic means to achieve mutual intelligibility and maximum communicative effectiveness. The interaction of the ad hoc and dynamic conditions results in the development of properties that become typical for communicative encounters, where successful communication and mutual intelligibility are the goals. ELF interaction is thus characterized by the presence of properties relating to communicative success and mutual understanding, often making these communicative encounters ‘distinct’. The paper argues, drawing on spontaneous spoken production of Ukrainian, Russian and Polish speakers of English, that ‘distinct’ properties of ELF interactions emerge due to the realization of the Principle of Relevance. If the Principle of Relevance guides speakers in their search for appropriate communicative strategies and means of expression, then this supports the view that communication in English as a Lingua Franca follows the principles of any human communication and contributes to conceptualizing ELF as natural human communication. As non-native speakers of English understand the nature of ELF interactions and its scope, namely participants’ limited communicative resources and mismatches in the common ground, they explicate and simplify their utterances, switch to other languages shared by the hearers, and accommodate to the hearers in terms of vocabulary, grammar and pronunciation. Doing so, speakers intuitively follow the Cognitive Principle of Relevance and the relevance-theoretic production strategy, allowing their interlocutors to process utterances and make inferences at low costs. The emergence of ELF-specific features, relating to achieving mutual intelligibility and maximum communicative effectiveness, such as the explicitness of proposition, accommodation, paraphrase and translanguaging are explained in terms of explicatures in the areas of free enrichment, reference assignment, disambiguation and ad hoc concept construction that contribute to providing a comprehensible input to the hearer. The paper is exploratory in suggesting directions that ELF research could further pursue.